A randomized controlled trial of a walking training with simultaneous cognitive demand (dual‐task) in chronic stroke. (25th November 2018) - Meester, D.; Al‐Yahya, E.; Dennis, A.; Collett, J.; Wade, D. T.; Ovington, M.; Liu, F.; Meaney, A.; Cockburn, J.; Johansen‐Berg, H.; Dawes, H.
Abstract : Background and purpose: The aim was to evaluate the tolerability of, adherence to and efficacy of a community walking training programme with simultaneous cognitive demand (dual‐task) compared to a control walking training programme without cognitive distraction. Methods: Adult stroke survivors at least 6 months after stroke with a visibly obvious gait abnormality or reduced 2‐min walk distance were included in a two‐arm parallel randomized controlled trial of complex intervention with blinded assessments. Participants received a 10 week, bi‐weekly, 30 min treadmill programme at an aerobic training intensity (55%–85% heart rate maximum), either with or without simultaneous cognitive demands. Outcome was measured at 0, 11 and 22 weeks. The primary assessment involved 2‐min walk tests with and without cognitive distraction to investigate the dual‐task effect on walking and cognition; secondary results were the Short Form Health Survey 36, EuroQol‐5D‐5L, the Physical Activity Scale for the Elderly (PASE) and step activity. Results: Fifty stroke patients were included; 43 received allocated training and 45 completed all assessments. The experimental group ( n = 26) increased their mean (SD) 2‐min walking distance from 90.7 (8.2) to 103.5 (8.2) m, compared with 86.7 (8.5) to 92.8 (8.6) m in the control group, and their PASE score from 74.3 (9.1) to 89.9 (9.4), compared with 94.7 (9.4) to 77.3 (9.9) in the control group. Statistically, only the change in the PASE differed between the groups ( P = 0.029), with the dual‐task group improving more. There were no differences in other measures. Conclusions: Walking with specific additional cognitive distraction (dual‐task training) might increase activity more over 12 weeks, but the data are not conclusive.